Incidental temporal binding in rats: A novel behavioral task - Radostova, Dominika; Kuncicka, Daniela; Krajcovic, Branislav; Hejtmanek, Lukas; Petrasek, Tomas; Svoboda, Jan; Stuchlik, Ales; Brozka, Hana (PloS one, 2023)
We designed a behavioral task called One-Trial Trace Escape Reaction (OTTER), in which rats incidentally associate two temporally discontinuous stimuli: a neutral acoustic cue (CS) with an aversive stimulus (US) which occurs two seconds later (CS-2s-US sequence). Rats are first habituated to two similar environmental contexts (A and B), each consisting of an interconnected dark and light chamber. Next, rats experience the CS-2s-US sequence in the dark chamber of one of the contexts (either A or B); the US is terminated immediately after a rat escapes into the light chamber. The CS-2s-US sequence is presented only once to ensure the incidental acquisition of the association. The recall is tested 24 h later when rats are presented with only the CS in the alternate context (B or A), and their behavioral response is observed. Our results show that 59% of the rats responded to the CS by escaping to the light chamber, although they experienced only one CS-2s-US pairing. The OTTER task offers a flexible high throughput tool to study memory acquired incidentally after a single experience. Incidental one-trial acquisition of association between temporally discontinuous events may be one of the essential components of episodic memory formation.
Keywords: rozpomínání; úniková reakce; vydry; krysa rodu Rattus; Otters; Escape Reaction; Animals; Fear; strach; Mental Recall; zvířata; Rats